2019
DOI: 10.2147/ott.s199508
|View full text |Cite
|
Sign up to set email alerts
|

<p>miR-21: a promising biomarker for the early detection of colon cancer</p>

Abstract: Purpose The aim of this study was to compare the expression of miR-21 gene in stages II-IV of formalin-fixed paraffin-embedded (FFPE) tissue in patients with colon cancer and introduce miR-21 as a potential molecular marker for detection of colon cancer in the early stages. Introduction Currently, identification of key molecules involved in the pathogenesis of cancer is one of the areas under consideration. miRNAs, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 45 publications
(46 reference statements)
0
10
0
Order By: Relevance
“…Plenty of studies have proven that miR-21 participates in the occurrence and development of tumors [ 79 , 80 ], cardiovascular [ 81 ] and lung diseases [ 82 , 83 ], glaucoma intraocular pressure [ 84 ], age-related skin wound healing [ 85 ], sepsis, and acute kidney injury [ 86 ]. Moreover, it is expected to be a potential marker for the diagnosis of diseases, such as colon cancer [ 87 ], liver cancer or hepatitis severity [ 88 ], colorectal cancer [ 89 ], and lung adenocarcinoma [ 90 ]. The expression of miR-21 was significantly elevated at 1, 4, 7, and 14 days after PNI and was able to regulate the gene expression of the sciatic nerve stump [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plenty of studies have proven that miR-21 participates in the occurrence and development of tumors [ 79 , 80 ], cardiovascular [ 81 ] and lung diseases [ 82 , 83 ], glaucoma intraocular pressure [ 84 ], age-related skin wound healing [ 85 ], sepsis, and acute kidney injury [ 86 ]. Moreover, it is expected to be a potential marker for the diagnosis of diseases, such as colon cancer [ 87 ], liver cancer or hepatitis severity [ 88 ], colorectal cancer [ 89 ], and lung adenocarcinoma [ 90 ]. The expression of miR-21 was significantly elevated at 1, 4, 7, and 14 days after PNI and was able to regulate the gene expression of the sciatic nerve stump [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, growing evidence has demonstrated that miRNAs function as diagnostic and/or prognostic biomarkers in certain patients with cancer, such as colon cancer and hepatocellular carcinoma (31,32). In glioma, studies have indicated aberrantly expressed miRNAs are correlated with clinical progression and patient survival, such as miR-3653 (33), miR-362-3p (34) and miR-526b-3p (35).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has demonstrated that miRNAs are frequently aberrantly expressed in various cancers and are associated with tumor progression and survival of various cancers 1921. For instance, the miR-629-3p expression is upregulated in human lung adenocarcinoma tissues and cell lines, and it promotes cell proliferation and predicts poor survival in lung adenocarcinoma 22.…”
Section: Discussionmentioning
confidence: 99%